Pembentukan Aktor Pemula Melalui Program Praktisi Mengajar Pada Program Studi PBSI Universitas Sarjanawiyata Tamansiswa - Pramasheilla, Dinda Assalia Avero; Handayani, Lusi; Vanacova, Sherin Adelia Avero; Gena, Sekar; Puspita, Oktaviani Windra (Universitas Jambi, 2026)
The learning of the Stage Production course in the PBSI Study Program at Universitas Sarjanawiyata Tamansiswa faces challenges in preparing students as beginner actors, particularly in integrating theoretical understanding with acting practice. This research aims to explore strategies for developing beginner actors through the combination of basic training and performance preparation within the framework of the Teaching Practitioner Program. Using a descriptive qualitative method, this research positions the researcher as the primary instrument to capture learning dynamics holistically through participatory observation, interviews, and documentation. The research subjects consisted of 30 students from the Stage Production class and the course lecturer, with data analyzed using the Miles, Huberman, and Saldaña model through three stages: data reduction, data display, and conclusion drawing. The findings reveal that the synergy between the training phase (body training, vocal training, emotional training) and the rehearsal phase (reading text, cut-to-cut, run through) significantly builds students' performative readiness. The presence of practitioners strengthens this process by introducing professional theater working methods, which impact the improvement of discipline, collaborative abilities, and students' understanding of the complex theater production ecosystem. In conclusion, the integrative model between basic training and performance preparation within the Teaching Practitioner Program effectively develops beginner actors who are not only technically skilled but also possess collective awareness and strong character, while offering significant contributions to the development of performing arts education curricula in higher education institutions.